PENGARUH STRUKTUR MODAL, PROFITABILITAS, LEVERAGE DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Nathanael, Roy Fredirick; Panggabean, Rosinta Ria (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
One of the decisions to increase investor’s trust and prosperity is to increase the firm value. The firm value is the investor's perception of the success rate of a company that is often associated with stock prices. By increasing trust in investors, the firm value in a company will increase. The purpose of this study is to determine the effect of capital structure, profitability, leverage, and growth opportunity on the firm value. This study took a sample based on the purposive sampling method in the secondary sectors on the Indonesia Stock Exchange in 2014 - 2018. The number of samples obtained was 41 companies. The analysis technique used in the study is the classic assumption test and panel data regression analysis. The results of this study indicate that capital structure had a significant influence on the firm value, whereas profitability, leverage, and growth opportunity did not significantly influence the firm value.